Sexual harassment protocols at the European universities: An overview of key components and recommendations for improvement - Marina Berbegal-Bernabeu; Vanesa Pérez-Martínez; Mafalda Sousa; Sofia Neves; Anneleen De Cuyper; Stefano Porru; Angela Carta; Maryna Manchenko; Sylwia Jaskulska; Barbara Jankowiak; Marlies Wallner; Viktoria Stifter; et al. (PLoS ONE, 2026)
Protocols against sexual harassment (SH) have been widely adopted in European universities as part of a broader structural gender approach in higher education and research institutions. However, existing literature indicates that these protocols have often been insufficient. In particular, there is a lack of effective restorative measures that address the needs of both survivors and perpetrators of SH. The aim of this study was to analyse and compare SH protocols across seven European universities and to provide evidence-based recommendations for improving the management of SH in higher education. The study adopts an intersectional perspective, recognising how overlapping social factors (such as gender, ethnicity, disability, or migration status) shape experiences of SH. This study employed a qualitative content analysis, using content analysis of 10 SH protocols from seven European universities. The results show that some universities provide comprehensive protocols that include procedural, preventive, and reparative measures. However, others have protocols with significant shortcomings. These include limited implementation, diffuse procedures, and a lack of practical application of an intersectional approach. Main recommendations include offering multiple and accesible reporting and support resources, appointing a single case coordinator to accompany survivors throughout the entire process, and enhancing cooperation between departments and specialised external services addressing SH and sexual violence (SV).